-4.(-5):(-2)+{-4+(-2)-[5.(-2)]+3-(-5)}=???

12:(-2)+{-3+4-[5+(4:2)-10]-5+3}=???

-15:(-5)+{7.(-2)-[3-7-(6-10)-2]-4}=???

10.(-2)-{40:(-5)+[3-5-(-4+3)-2]}=???

18:(-3)-{2.(-4)+[-5+4-(7-3+2)-2+3]}=???

2.(-6)+15:(-5)+{4-5-[4+2-(-2.4)+3]}=???

2

Respuestas

2012-05-14T00:16:33+02:00

-4.(-5):(-2)+{-4+(-2)-[5.(-2)]+3-(-5)}=10

2012-05-14T01:12:09+02:00

12:(-2)+{-3+4-[5+(4:2)-10]-5+3}=

 

primero resolvemos los parentesis ok

12:(-2)+{-3+4-[5+2-10]-5+3}=

12:(-2)+{-3+4-[-3]-5+3}=

12:(-2)+{-3+4+3-5+3}=

12:(-2)+2=

12:(-2)+2=

-6+2=-4